The Effect of Integrating DARTs on Learners Academic Performance in Rates of Chemical Reacxtions - Peter Magawa; Kabaso Kennedy Kalebaila (Universitas Islam Indonesia, 2020)
This research examined the effect of integrating DARTs (Directed Activities Related to Texts) on learners’ academic performance in rates of chemical reactions at Raphael Kombe Secondary School in Kabwe, Zambia. A total of 105 participants (N=105) was assigned randomly into control and experimental groups. The control group was taught using collaborative method and the experimental group was taught using DARTs strategy. DARTs strategy is a teaching method which demands a learner centered activity in order to explain the terms and concepts in any science topic hence helps to break the science language barrier. Quantitative data was collected from both groups on three different times using Pre-test, Post-test and Counterbalance test. Quantitative data was tested for normality using Shapiro-Wilk test and normally distributed data was later tested using the Independent samples t-test to compare the achievement mean scores of the two groups.